A unique network of attack, defence and competence on the outer membrane of the periodontitis pathogen Tannerella forsythia. Issue 4 (3rd January 2023) - Książek, Mirosław; Goulas, Theodoros; Mizgalska, Danuta; Rodríguez-Banqueri, Arturo; Eckhard, Ulrich; Veillard, Florian; Waligórska, Irena; Benedyk-Machaczka, Małgorzata; Sochaj-Gregorczyk, Alicja M.; Madej, Mariusz; Thøgersen, Ida B.; Enghild, Jan J.; et al.
Abstract : Periodontopathogenic Tannerella forsythia possesses the unique, tightly-regulated KLIKK-peptidase/potempin system in which six distinct metallo- and serine peptidases are specifically inhibited by cognate potempins (Pot) A, B1, B2, C, D and E. Abstract : Periodontopathogenic Tannerella forsythia uniquely secretes six peptidases of disparate catalytic classes and families that operate as virulence factors during infection of the gums, the KLIKK-peptidases. Their coding genes are immediately downstream of novel ORFs encoding the 98–132 residue potempins (Pot) A, B1, B2, C, D and E. These are outer-membrane-anchored lipoproteins that specifically and potently inhibit the respective downstream peptidase through stable complexes that protect the outer membrane of T. forsythia, as shown in vivo . Remarkably, PotA also contributes to bacterial fitness in vivo and specifically inhibits matrix metallopeptidase (MMP) 12, a major defence component of oral macrophages, thus featuring a novel and highly-specific physiological MMP inhibitor. Information from 11 structures and high-confidence homology models showed that the potempins are distinct β-barrels with either a five-stranded OB-fold (PotA, PotC and PotD) or an eight-stranded up-and-down fold (PotE, PotB1 and PotB2), which are novel for peptidase inhibitors. Particular loops insert like wedges into the active-site cleft of the genetically-linked peptidases to specifically block them either via a new "bilobal" or the classic "standard" mechanism of inhibition. These results discover a unique, tightly-regulated proteolytic armamentarium for virulence and competence, the KLIKK-peptidase/potempin system.